KONTRIBUSI PENERAPAN PRODUCT BASED LEARNING TERHADAP KESIAPAN KERJA PESERTA DIDIK SMKN 6 BEKASI DI DUNIA KERJA INDUSTRI - Muhammad Aziz, - (2021)
The goal of this study case was to define: 1) To describe application of product based learning in group learning of productive subjects at SMKN 6 Bekasi. 2) Knowing information about the work readiness of students at SMKN 6 Bekasi. 3).Knowing information about the contribution of the application of product-based learning to the work readiness of students at SMKN 6 Bekasi in the industrial world. The variables in this study were the application of product-based learning as the independent variable, and the work readiness of students as the dependent variable. Methods of data collection use the questionnaire method. The results of the analysis show that: 1). Activity in extracurricular activities in class X DPIB SMKN 6 Bekasi for the 2020/2021 school year based on the results of the questionnaire distribution and calculations that the application of product-based learning is included in the "good enough" category. 2.) Work readiness of class XII students of DPIB SMKN 6 Bekasi for the 2020/2021 academic year based on the results of the distribution of questionnaires and calculations that work readiness is included in the "quite ready" category. 3). Based on the research that has been carried out, it is known that Ha is accepted and H0 is rejected. Meaning Significant. So, it can be seen that the variable X (application of product-based learning) has a significant contribution to the variable Y (work readiness). This means that in the study Ha is accepted and H0 is rejected. So, it can be concluded that there is a significant contribution to the application of product-based learning with the work readiness of class XII students of DPIB SMKN 6 Bekasi in the industrial world.